2017
DOI: 10.1016/j.ssresearch.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Tackling inequalities in political socialisation: A systematic analysis of access to and mitigation effects of learning citizenship at school

Abstract: This article tackles the issue of social inequalities in voting and identifies how and when differences in learning political engagement are influenced by social background in the school environment between the ages of 11-16 in England. Using Latent Growth Curve Modelling and Regression Analysis on the Citizenship Education Longitudinal (CELS) data this research identifies two elements that influence the political socialisation process: access to political learning and effectiveness in the form of learning in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 24 publications
3
42
0
1
Order By: Relevance
“…In Finland, in-school civic participation also compensated for inequalities in civic knowledge in 2009 by quite a considerable size. These results of the benefits of in-school civic participation is new to the field of citizenship education, as previous research has only found mitigating effects for citizenship education (Deimel et al 2020;Gainous and Martens 2012;Hoskins et al 2017;Hoskins and Janmaat 2019) or open classroom climates (Campbell 2008). Thus, we can conclude that the targeted provision of access to civic learning-in particular in-school civic participation-for less advantaged students can provide an important tool that schools can use to combat inequalities in civic competence and has the potential to reduce future inequalities in political engagement.…”
Section: What Should Schools Do To Reduce Inequalities In Civic Compementioning
confidence: 80%
See 2 more Smart Citations
“…In Finland, in-school civic participation also compensated for inequalities in civic knowledge in 2009 by quite a considerable size. These results of the benefits of in-school civic participation is new to the field of citizenship education, as previous research has only found mitigating effects for citizenship education (Deimel et al 2020;Gainous and Martens 2012;Hoskins et al 2017;Hoskins and Janmaat 2019) or open classroom climates (Campbell 2008). Thus, we can conclude that the targeted provision of access to civic learning-in particular in-school civic participation-for less advantaged students can provide an important tool that schools can use to combat inequalities in civic competence and has the potential to reduce future inequalities in political engagement.…”
Section: What Should Schools Do To Reduce Inequalities In Civic Compementioning
confidence: 80%
“…Several scholars have identified education's compensatory effects on aspects of civic competence (Campbell 2008;Castillo et al 2015;Deimel et al 2020;Gainous and Martens 2012;Hoskins et al 2017;Hoskins and Janmaat 2019). These scholars have mostly identified compensatory benefits in terms of students acquiring a greater amount of civic education (Deimel et al 2020;Gainous and Martens 2012;Hoskins et al 2017;Hoskins and Janmaat 2019). Campbell's (2008)…”
Section: The Role Of School In Reproducing Inequalities In Political mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, young people's mid and late adolescence is considered a critical period in the encouragement and shaping of political engagement (Feldman et al 2007;Hoskins, Janmaat, and Melis 2017). During these formative years, they establish crucial bases of political interest, efficacy, and deliberation that can help them in becoming active, democratic citizens (Dinas 2012;Eagles and Davidson 2001).…”
Section: Youth Engagement and Political Socializationmentioning
confidence: 99%
“…On the one hand, the data gathered by CELS showed that levels of exposure to citizenship education across secondary school significantly predict participants' civic engagement in terms of efficacy, current and anticipated participation, and political knowledge (Keating et al, 2010;Keating and Janmaat, 2016;Whiteley, 2014). Hoskins et al (2017) also utilise CELS data to highlight a compensatory effect in which citizenship education may mitigate socio-economic inequalities in political participation (for an international comparison, see Castillo et al, 2015). On the other hand, only 59.1% of CELS participants in 2011 (the first cohort to go through school with citizenship education) reported voting in 2010 (Keating and Kerr, 2013, p.3) and the proportion involved in their community declined from 33% in 2009 (when the students were in their final year of school) to just 15% in 2011.…”
Section: Citizenship Education 1998-presentmentioning
confidence: 99%